A thematic analysis of selected archives in Metro Manila academic libraries for the establishment of Miriam College Archives - Tamayo, Maria Chezka G. (Animo Repository, 2022)
This study aimed to determine the significance of establishing an archive in Miriam College that will facilitate the documentation and safekeeping of different materials that are rare, unique, and valuable to the institution. A descriptive qualitative research approach through Case Study and purposive sampling methods were implemented to gather data. A total of ten (10) participants were interviewed composed of three (3) archivists and seven (7) librarians from different colleges and universities in Metro Manila. The purpose of the interview was to develop in-depth knowledge and appreciation of the importance of establishing an archive. The interview sessions were conducted virtually via Google Meet and Viber messenger chat application. Thematic coding was used to analyze the transcript of responses and extract themes that emerged in the study. The research findings revealed that 100% of the participants affirmed that the organization and management of archives is very important and of good advantage for an academic institution. The funding depends on the type of institution: it can be included in the library budget, directly under the school’s administration and the provision of a government agency. The study also described multiple challenges cited by the respondents nevertheless there lie various strategies that can be implemented. The outcome of this research was utilized as a basis for the creation of a proposal to the administration of Miriam College toward the organization of archives. A further study on the implications and utilization of technologies that will facilitate the accessibility of information and materials in archives was recommended.